2010
DOI: 10.1007/s10212-010-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Fostering active processing of instructional explanations of learners with high and low prior knowledge

Abstract: Despite the potential advantages of instructional explanations, evidence indicates that they are usually ineffective. Subsequent work has shown that in order to make instructional explanations effective indeed, one successful strategy is to combine them with indications of the limitations in learners" understanding that they are intended to revise, which makes learners deeply process the explanations. We explored whether this is so for both learners with low and those with high prior domain knowledge. In one e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Thus, in terms of the active-constructive-interactive framework [ 6 , 7 ], these learners rarely engaged in interactive learning activities in response to engaging prompts. Additionally, the learners scarcely benefitted from remedial explanations [ 33 34 ]. In order to overcome this deficiency, Sánchez and colleagues combined remedial explanations with prompts that were designed to induce revision-oriented learning activities (i.e., revision prompts) [ 20 , 21 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in terms of the active-constructive-interactive framework [ 6 , 7 ], these learners rarely engaged in interactive learning activities in response to engaging prompts. Additionally, the learners scarcely benefitted from remedial explanations [ 33 34 ]. In order to overcome this deficiency, Sánchez and colleagues combined remedial explanations with prompts that were designed to induce revision-oriented learning activities (i.e., revision prompts) [ 20 , 21 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In order to overcome this deficiency, Sánchez and colleagues combined remedial explanations with prompts that were designed to induce revision-oriented learning activities (i.e., revision prompts) [ 20 , 21 ]. In several studies, they consistently found that remedial explanations plus revision prompts fostered both learning outcomes [ 33 , 34 ] and revision-oriented processing of the explanations [ 17 ] as compared to providing remedial explanations plus engaging prompts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this context, evocations and refutations (as discussed earlier) can also indicate what readers must learn. For example, if a misconception is identified by means of a refutation, then readers can assume that the text was created to correct it. There are devices intended to encourage readers to detect possible misunderstandings in the ongoing processes, such as warning messages (Acuña, García‐Rodicio & Sánchez, ; Sánchez, García‐Rodicio & Acuña, ): ‘Usually, people tend to elaborate a simplified conception … However, there are important differences …’. A warning message indicates a comprehension problem while reading (not in prior knowledge).…”
Section: The Contribution Of Rhetorical Devices To Expository Texts Cmentioning
confidence: 99%
“…In addition, it enables readers to form a coherent representation (Degand & Sanders, ) even when they have adequate decoding skills but poor comprehension skills (Meyer, Brandt & Bluth, ). Refutations, objectives, questions and warning messages have also been shown to be useful, especially when texts are difficult or when counterintuitive scientific material is provided (Acuña et al, ; Alvermann & Hague, ; Diakidoy et al, ; Dole, ; Hynd, ; Linderholm et al, ; Reynolds & Anderson, ; Rothkopf & Kaplan, ; Sánchez et al, ).…”
Section: The Contribution Of Rhetorical Devices To Expository Texts Cmentioning
confidence: 99%
“…Durkin and Rittle-Johnson ( 2012 ) found that comparing common mathematical errors to correct examples increases learning in comparison to comparing only correct examples. Further research demonstrated that students process the canonical solution more deeply when they realize impasses and errors (van Lehn et al 2003 ) and that the realization of an impasse can be triggered by the warning of possible errors before presenting the instructional explanation (Acuña et al 2010 ;Sánchez et al 2009 ). Taking these fi ndings together, it seems promising to investigate the role of typical student-generated, non-canonical solutions in instruction prior to problem-solving approaches.…”
Section: Focusing Attention During Instructionmentioning
confidence: 99%